THE IMPACT OF THE PANDEMIC COVID-19 ON THE FREQUENCY OF SHOPPING AND ONLINE SALE OF ORGANIC FOOD AMONG CONSUMERS OF THE FORMER YUGOSLAVIA: UTICAJ PANDEMIJE COVID-19 NA UČESTALOST KUPOVINE I ONLINE PRODAJU ORGANSKE HRANE MEĐU POTROŠAČIMA BIVŠE JUGOSLAVIJE - Mitić, Vladimir; Čolović, Milica (Food and Feed Research, 2023)
The main goal of this research is to determine the impact of the Covid-19 Pandemic on the frequency of buying organic food. It also examines whether the online sale of organic food has increased, and which channels were used for its purchase. The sample in the current research consists of 400 respondents of different demographic characteristics who filled out the questionnaire on two occasions, in 2020 and 2022. Data was processed in the SPSS program, and in addition to descriptive statistics, non-parametric techniques, the Wilcoxon test of equivalent pairs and the Kruskal-Wallis test were used to determine the differences in scores between several groups of respondents. The results showed that due to the impact of the Covid-19 pandemic, the frequency of buying organic food increased as its sale via the Internet. Consumers buy organic food most often in supermarkets and hypermarkets, while only few consumers buy it directly from organic food producers.